Implicit tax co-ordination under repeated policy interactions - Marco Catenaro; Jean-Pierre Vidal (European Central Bank (ECB), 2003)
In the context of a stylised game theoretical framework of capital tax competition, we show that when repeated policy interactions are associated to a systematic punishment of the deviating policymaker, a co-ordinated outcome can be the solution to the non co-operative tax game. This result suggests that explicit forms of policy co-ordination, such as a centralised tax authority, could in fact be largely unnecessary.
Keywords: E61; H87; 330; International Fiscal Issues; Policy Co-ordination